Stać przed zagadkami świata i życia ludzkiego bez gotowych odpowiedzi. O pisaniu biografii (nie tylko) Jana Potockiego - Borowczyk, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The conversation concerns the broadly-understood methodological background and substantive knowledge of the co-author of the highly praised biography of Jan Potocki, François Rosset. The researcher talks about the importance and usefulness of knowledge of the French eighteen-century novel, the Enlightenment ideas and artistic trends for the work on the biography of the author of The Manuscript found in Saragossa. Rosset also talks about archive research related to the work on this biography and about how he used his knowledge of editorial meanders of the famous novel while writing. The researcher emphasizes that the authors of biographies should keep a distance from the characters of their stories and that their main goal is to try to present the life cycle of a given person as comprehensively as possible, supporting it with sources.